2021
DOI: 10.3233/jpd-202279
|View full text |Cite
|
Sign up to set email alerts
|

Infection and Risk of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is thought to be caused by a combination of genetic and environmental factors. Bacterial or viral infection has been proposed as a potential risk factor, and there is supporting although not entirely consistent epidemiologic and basic science evidence to support its role. Encephalitis caused by influenza has included parkinsonian features. Epidemiological evidence is most compelling for an association between PD and hepatitis C virus. Infection with Helicobacter pylori may be associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 106 publications
1
84
1
1
Order By: Relevance
“…Viral infections were proposed as potential risk factors for PD, and there is supporting although not entirely consistent epidemiological and basic science supporting evidence (review Ref. 97 ). In a multihit hypothesis of PD, Sadasivan et al demonstrated that prior exposure of mice to non-neurotropic pandemic influenza A/California/04/2009 H1N1 virus, which triggers brain inflammation, exacerbates their vulnerability to a parkinsonian toxin, MPTP, 1 month later, resulting in heightened loss of DA neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Viral infections were proposed as potential risk factors for PD, and there is supporting although not entirely consistent epidemiological and basic science supporting evidence (review Ref. 97 ). In a multihit hypothesis of PD, Sadasivan et al demonstrated that prior exposure of mice to non-neurotropic pandemic influenza A/California/04/2009 H1N1 virus, which triggers brain inflammation, exacerbates their vulnerability to a parkinsonian toxin, MPTP, 1 month later, resulting in heightened loss of DA neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The main pathological features of PD are degeneration of nigrostriatal dopaminergic neurons, reduction of striatal dopamine, and the formation of abnormal protein aggregates in neurons, such as Lewy vesicles. The aging nervous system is susceptible to the direct and indirect effects of infection, and bacterial or viral infections are considered a potential risk factor ( Pajares et al, 2020 ; Hirsch and Standaert, 2021 ; Smeyne et al, 2021 ). Predominantly lymphocytic leukocytosis, mildly increased protein levels, and EBV antibodies in the CSF and serum of patients with PD suggest the involvement of EBV infection in the development of PD ( Bu et al, 2015 ; Schroder et al, 2018 ).…”
Section: Ebv and Parkinson’s Diseasementioning
confidence: 99%
“…Studies have demonstrated an increased risk of Parkinson's disease in Hp-positive patients, while the eradication of the bacterium doesn't seem to contribute to the reduction of the risk [58]. The overproduction of interleukin 17 (IL-17) and interferon-gamma (INF-Y) release can be related to reduced hippocampal neurogenesis and destruction of the myelin sheath, respectively.…”
Section: Extragastric Manifestations: Neurological Cardiac and Vascular And Endocrine Diseases Neurological Diseasementioning
confidence: 99%